Entrevista - George P. Lakoff - Abreu, Helen de Andrade (Programa de Pós-graduação em Linguística da Universidade Federal do Rio de Janeiro (UFRJ), 2016)
George Lakoff is one of the most widely recognized and celebrated scholars in the field of Cognitive Linguistics in the world today. And with good reason, because Lakoff not only helped pioneer this field from its earliest beginnings, but also he has guided and shaped its development down to thepresent day.